La petite pêche en Aquitaine - le bassin d'Arcachon - Halieutique, socio-économie, usages et réglementations. 1999-2000 - Caill-milly, Nathalie; Leaute, Jean-pierre; Trouillet, Brice; Laborde, Jean-louis; Goumy, Cécilia; Prouzet, Patrick; Grandpierre, Alde; Lissardy, Muriel; Corlay, Jean-pierre (2001)
Introduction : Intra-basin fishing is not grasped as well, partly because of a lack of distinction between pure professional fishing units and conchological units and on the other hand because of the large amount of ships. Poorly adapted codification of the equipment found in the basin is also contributing to this lack of information. Studies on the subject do exist, but the elements necessary to publish notices are not always gathered, this is leading to the proposal of a geographical systemic analysis on the basin. The steps that are being taken are complementing the development of the Geographical Information System already in place in the basin since 1993 through DEL at the Arcachon Ifremer as well as the PECOSUDE European study ¿ caractéristiques des petites PÊches CÔtières et estuariennes de la côte atlantique du SUD de l'Europe ¿ (characteristics of small coastal and estuarine fishing on the south Atlantic coast of Europe). The topics that are covered are as follows: ¿ description of the intra-basin halieutic activity and presentation of the socio-economic indicators elaborated from CRTS' information and an exhaustive survey conducted on board some 547 ships in the basin.; ¿ mapped representation of the fishing activity and other uses such as recreational boating, oyster farming and protection perimeters of the environment applicable in the basin; ¿ synthesis of main species biology found in the Arcachon basin, i.e. European eel, common bass, royal sea bream, thicklip mullet and gold mullet, thornback ray and painted ray, silt red mullet , common cuttlefish and common sole; ¿ synthesis of current regulations for intra-basin fishing. The themes discussed are about administrative organisation, crews, ships, machinery, licensing system, sanitary conditions and the sale of sea products. Upon the completion of this work, a general synthesis will aim at bringing forth the previous major points. At the request of fishing professionals, the study was complemented by a specific part concerning clams. The goal of ...